GROWING THE SPIRIT OF LITERATION IN CHILDREN WITH LISTENING - Fitriah, Nurlaeli (Proceeding of International Conference on Islamic Education (ICIED); Vol 2 No 1 (2017): Proceeding of International Conference on Islamic Education (ICIED), 2017)
Begins from concerns of the increasing negative impact of technological advances on children's behavior, especially children at school, government through the ministry of education and culture, launched a program to build a culture of literacy in schools. Literacy is implemented to grow up reading interest of children who have down and down over time. And this have affected the child's behavior. This culture has started running in some schools by cultivating reading 15 minutes before the lesson. For early childhood reading activities are not identical with their age. However, by building the spirit of literacy early on in children would be easier to grow their reading interest in school age later. Many ways and tips that can be used to build the spirit of literacy in early childhood. One of the way that can be used is to give the time to listen to everything they want to say without being cut off in the middle of they said. Letting them pour out all their hearts and appreciate them will increase their literacy spirit.